2023
DOI: 10.53300/001c.70233
|View full text |Cite
|
Sign up to set email alerts
|

Domestic and Family Violence and Private Family Report Writing Practice in the Australian Family Law System: A Study

Abstract: In Australia, family reports are an influential expert assessment of a family usually undertaken in contentious family law parenting matters by social workers or psychologists, known as family report writers. This article presents findings from in-depth interviews with 10 private family report writers about their experience of undertaking assessments, particularly in cases where domestic and family violence is alleged. The study reveals a number of concerns that mirror the findings of previous Australian and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…The most recent review of the 2012 Family Law Act amendments 1 , conducted by the Australian Institute for Family Studies (Kaspiew et al, 2015), revealed that almost one third of parents being surveyed about their experiences of Family Law proceedings had reportedly never been asked about IPV or related safety concerns throughout the process. While the most recent reforms stipulate that IPV needs to be identified early in the process to better protect women in the actual hearing, cases of re-traumatisation as part of the proceeding still occur (Douglas, 2018; Jeffries, Field, Menih, & Rathus, 2016). This may partly be the result of many couples not being asked about IPV during the early stages of family law proceedings and the assumption in the legal paradigm that situational couple violence (SCV) occurs as a result of mutual conflict, which has minimal impact (Jeffries et al, 2016; Meier, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The most recent review of the 2012 Family Law Act amendments 1 , conducted by the Australian Institute for Family Studies (Kaspiew et al, 2015), revealed that almost one third of parents being surveyed about their experiences of Family Law proceedings had reportedly never been asked about IPV or related safety concerns throughout the process. While the most recent reforms stipulate that IPV needs to be identified early in the process to better protect women in the actual hearing, cases of re-traumatisation as part of the proceeding still occur (Douglas, 2018; Jeffries, Field, Menih, & Rathus, 2016). This may partly be the result of many couples not being asked about IPV during the early stages of family law proceedings and the assumption in the legal paradigm that situational couple violence (SCV) occurs as a result of mutual conflict, which has minimal impact (Jeffries et al, 2016; Meier, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While the most recent reforms stipulate that IPV needs to be identified early in the process to better protect women in the actual hearing, cases of re-traumatisation as part of the proceeding still occur (Douglas, 2018; Jeffries, Field, Menih, & Rathus, 2016). This may partly be the result of many couples not being asked about IPV during the early stages of family law proceedings and the assumption in the legal paradigm that situational couple violence (SCV) occurs as a result of mutual conflict, which has minimal impact (Jeffries et al, 2016; Meier, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations